PERAN PEMERINTAH INDONESIA DALAM MENGATASI KEKERASAN BERBASIS GENDER ONLINE (KBGO) TAHUN 2015-2022 - Tihanum, Diara; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research analyzes the role of the Indonesian government in overcoming online gender-based violence (KBGO) 2015-2022. The increase in the number of KBGO cases from 2015-2022 indicates that many women in Indonesia are not receiving justice and their rights to access the internet, the right to free expression and the right to feel safe. Qualitative methods are used to see Indonesia's commitment to implementing Anti-OGBV norms through the Convention on the Elimination of All forms of Discrimination Against Women (CEDAW). causes, characteristics or forms, and the number of OGBV cases in Indonesia 2015-2022. Through several journal articles, SAFEnet reports, the awaskbgo website, institutional documents and the National Commission on Violence Against Women's Annual Notes. The Indonesian Government's policy to address OGBV is analyzed from legislative policies such as the Criminal Code Law (KHUP), the Information and Technology Law (UU ITE), and the Sexual Crimes Law (UU TPKS). Keywords: Online Gender Based Violence (OGBV), Internalization of Norms, Role of the Indonesian Government.